Activity Test of Cinnamon Extract (Cinnamomumzeylanicum) and Bay Leaf (Syzygiumpolyanthum) and Their Combination as Antidiabetic in Vivo - Syahfitri, Shella; Silalahi, Jansen; Sinaga, Hotnida (Asian Journal of Pharmaceutical Research and Development, 2023)
Diabetes Mellitus (DM) is a chronic disorder of carbohydrate (glucose) metabolism in the body and its prevalence is getting higher. Until 2015, 10 million cases of DM were found in Indonesia and allegedly continue to increase. Currently, the Indonesian government encourages people to consume traditional medicines because they remember the low side effects. Cinnamon (Cinnamomumzeylanicum) contains antioxidants that can reduce the risk of oxidative stress, a condition that is a major risk factor for several chronic diseases, including diabetes. Bay leaf (Syzygiumpolyanthum) also contains flavonoids that can lower glucose levels. Thus, cinnamon and bay leaves have the potential to be products that are beneficial to the community, namely diabetic herbal medicine. The purpose of this study was to determine the antidiabetic activity of cinnamon bark extract (Cinnamomumzeyl anicum) and bay leaf extract (Syzygiumpolyanthum) against reducing blood sugar levels in test animals. This study used experimental methods in vivo. Using 28 alloxan-induced male mice were divided into 7 groups: (1) Negative control without treatment, (2) Positive control given metformin 45mg/kgBB, (3) Cinnamon dose 750 mg/kgBB, (4) Bay leaf 750 mg/kgBB, (5) Combination of Cinnamon and Bay Leaf dose ratio 1: 1 (375 mg/kgBB), 1: 2 (250 mg/kgBB and 500 mg/kgBB), and 2:1 (500 mg/kgBB and 250 mg/kgBB), given orally for 14 days. The results showed a percentage decrease in blood sugar levels during the test obtained Metformin administration 32.27%, cinnamon by 24.52%, bay leaf 21.05%, combination (1: 1) 23.71%, (1: 2) 35.83%, (2: 1) 40.83%.